Accreditation is Perceived to Improve the Quality of Vascular Testing Facilities. Issue 2 (June 2016) - Brinza, Ellen K.; Zhu, Linda J.; Lilly, Michael; Manning, Warren J.; Needleman, Laurence; Gornik, Heather L.
Objective: Accreditation for noninvasive vascular testing facilities has been available since 1990, but is not mandatory. We sought to determine the perceived value of accreditation among the staff of vascular laboratories accredited by the Intersocietal Accreditation Commission (IAC). Methods: A multi-item electronic survey was sent to medical and technical staff and administrative contacts within the IAC database. Respondents were asked to rate statements about the impact of accreditation on their facility. Data for vascular testing facilities are presented. Results: Of the 7, 289 surveys sent, there were 882 (12.1%) respondents. Respondents were primarily responsible for the facility's accreditation application (75.0%), with the majority being technologists (82.0%), followed by physicians (11.3%). Most respondents were from hospital-based facilities (51.1%) and from facilities accredited for >3 years (79.6%). The majority, 94.3% of respondents, felt that maintaining accreditation of their facility was important (3.5% neutral, 2.2% not important). The greatest perceived benefits were in standardization of study acquisition and reporting, adherence to guidelines, and report completeness. Conclusions: The majority of respondents from IAC-accredited vascular testing facilities viewed accreditation favorably. The favorable perception of accreditation by its users supports the value of accreditation for vascular testing facilities.